The Impact Of Tax Aviodance On The Value Of A Company - Harahap, Subur (Journal of Management, 2024)
One of a company's objectives is to maximize the value of its shares by raising their price. This research looks at how leverage, financial performance, and tax evasion affect company value in manufacturing businesses listed on the Indonesia Stock Exchange from 2021 to 2023. In this study, purposive sampling was utilized. The requirements were satisfied by a total of 218 firms as observation units. Multiple linear regression analysis is used. The study's findings demonstrate that financial success has an impact on firm value. Meanwhile, tax evasion and leverage do not influence the firm value